2001
DOI: 10.2118/74138-pa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Fracture Conductivity for Water-Fracturing and Conventional Fracturing Applications

Abstract: Summary Hydraulic fracturing treatments that use treated water and very low proppant concentrations (commonly referred to as water-fracturing treatments or "waterfracs") have been successful in stimulating low-permeability reservoirs. However, the mechanism by which these treatments provide sufficient conductivity is not well understood. To understand the effects of fracture properties on conductivity, a series of laboratory conductivity experiments was performed with fractured cores from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(51 citation statements)
references
References 17 publications
3
47
0
Order By: Relevance
“…Maloney et al (1989) showed that the proppant packs may crush under stress leading to reduction in the fracture porosity. Likewise, Fredd et al (2001) presented laboratory data showing the effect of closure stress on propped fracture conductivity for a rock with relatively high Young's modulus. Therefore, recent studies such as Rubin (2010) and Cipolla et al (2010) used specific closure-stressconductivity tables in the simulation of unconventional reservoirs to account for the dynamic behavior of hydraulic fractures.…”
Section: Deformation Of Propped Hydraulic Fracturesmentioning
confidence: 99%
“…Maloney et al (1989) showed that the proppant packs may crush under stress leading to reduction in the fracture porosity. Likewise, Fredd et al (2001) presented laboratory data showing the effect of closure stress on propped fracture conductivity for a rock with relatively high Young's modulus. Therefore, recent studies such as Rubin (2010) and Cipolla et al (2010) used specific closure-stressconductivity tables in the simulation of unconventional reservoirs to account for the dynamic behavior of hydraulic fractures.…”
Section: Deformation Of Propped Hydraulic Fracturesmentioning
confidence: 99%
“…The displaced fractures have irregular surfaces and therefore do not completely match after closure. Laboratory and field tests have reported residual fracture widths that can be attributed to the combined effects of surface roughness and fracture displacement of the rock (Branagan et al, 1996;Van Dam and de Pater, 1999;Fredd et al, 2001). There are multiple mechanisms of propped fracture conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The second dataset is collected from the published literature by Fredd et al (2001). In their work, they measured the proppant size distribution after the conductivity experiment at 7000 psi closure stress.…”
Section: Validation Of the Solutionmentioning
confidence: 99%